The chemistry of the pedoderm – part 1: grasslands and savannas in the central Kruger National Park, South Africa. Issue 4 (2nd October 2022) - Mills, Anthony J; Strydom, Tercia; Allen, Jessica L; Baum, Julia
Abstract : Treeless grasslands occur within landscapes that are predominantly wooded savannas in the central Kruger National Park, South Africa. As a first step in identifying soil properties potentially underpinning differences in vegetation structure in these landscapes, we analysed the soil chemistry of the pedoderm (0–2 cm) in a grassland and two adjacent savanna types (Senegalia savanna and Delagoa Lowveld). The grassland was significantly enriched in P, Ca, Mg and Cu relative to both the savannas (1.8- and 5.8-fold for the Senegalia and Delagoa Lowveld savannas, respectively, for P; 1.8- and 5.7-fold for Ca; 1.7- and 6.0-fold for Mg; and 1.3- and 9.4-fold for Cu). It was also richer in Na (4.7-fold), Mn (6.3-fold) and Zn (1.6-fold) than the Delagoa Lowveld savanna. The competitive strength and nutritive value of the herbaceous layer in the grassland is likely to be greater than in the savannas because of the relative nutrient richness of the grassland's pedoderm. Herbivory pressure is also likely to be greater in the grassland because of the greater nutritive value of the herbaceous layer. These effects provide a plausible mechanism for the constraint of trees in the grassland.